2011
DOI: 10.2165/11585890-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Epolamine plus Heparin Plaster versus Diclofenac Epolamine Plaster in Mild to Moderate Ankle Sprain

Abstract: The fixed-dose DHEP/heparin plaster is effective and has advantages over the DHEP plaster in relieving pain, and possibly also swelling, associated with mild to moderate acute ankle sprains with oedema in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…19 The combination of diclofenac epolamine and heparin in the same patch formulation (DHEP+H), applied for several days (n = 7) to patients with an acute ankle sprain, has proven more effective than DHEP alone in reducing pain symptoms, an effect attributed mainly to the reduction in the local edema due to heparin. 20 Based on these data, the aim of this study was to verify whether the DHEP+H combination, applied for 7 days is more effective than DHEP alone in desensitizing deep somatic tissues in subjects who present hyperalgesia at this level (subcutis and muscle) but who do not complain of spontaneous pain, and in the case of a positive response, whether this effect is linked to or independent of an action onto the thickness/consistency of the examined tissues. To this aim, we assessed the possible changes, due to therapy, in pain thresholds to electrical and pressure stimulation of the somatic tissues in a body area presenting deep hyperalgesia in basal conditions and in tissue structure/thickness at ultrasounds.…”
mentioning
confidence: 99%
“…19 The combination of diclofenac epolamine and heparin in the same patch formulation (DHEP+H), applied for several days (n = 7) to patients with an acute ankle sprain, has proven more effective than DHEP alone in reducing pain symptoms, an effect attributed mainly to the reduction in the local edema due to heparin. 20 Based on these data, the aim of this study was to verify whether the DHEP+H combination, applied for 7 days is more effective than DHEP alone in desensitizing deep somatic tissues in subjects who present hyperalgesia at this level (subcutis and muscle) but who do not complain of spontaneous pain, and in the case of a positive response, whether this effect is linked to or independent of an action onto the thickness/consistency of the examined tissues. To this aim, we assessed the possible changes, due to therapy, in pain thresholds to electrical and pressure stimulation of the somatic tissues in a body area presenting deep hyperalgesia in basal conditions and in tissue structure/thickness at ultrasounds.…”
mentioning
confidence: 99%
“…Topical diclofenac and ibuprofen have been shown to be effective in acute soft tissue injuries, such as ankle sprains as well as arthritic knee pain [68,72,73]. Furthermore, topical diclofenac has been shown to be effective in reducing myofascial pain, however, with no effect on the myofascial trigger point pain threshold [74].…”
Section: Topical Analgesicsmentioning
confidence: 99%
“…Furthermore, topical diclofenac has been shown to be effective in reducing myofascial pain, however, with no effect on the myofascial trigger point pain threshold [74]. Topical NSAIDs have been shown to have equal efficacy as oral NSAIDs, yet various studies have shown topical diclofenac to reduce pain within 2-3 days of treatment [72,[75][76][77].…”
Section: Topical Analgesicsmentioning
confidence: 99%
“…Also there is some evidence that combinations of topical (co)analgesics lead to a more pronounced pain reduction compared to topical monotherapy [30][31][32]. Influencing multiple receptors and/or enhancing affinities of the main analgesic compounds might be the explanation for pronounced pain reduction.…”
Section: More Pronounced Analgesiamentioning
confidence: 99%